The Effect Of Ability, Motivation, and Job Satisfaction On Employee Performance at PT. Telkom Akases Banda Aceh Area (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This study aims to determine and analyze the influence of Ability, Motivation, and Job Satisfaction on Employee Performance at PT. Telkom Akses Area Banda Aceh. This research is associative in nature. The data used consists of primary data obtained directly from respondents through questionnaires, interviews, and observations, as well as secondary data sourced from internet sites, documentation studies, and company documents relevant to the object of study. The research involved a sample of 82 employees at PT. Telkom Akses Area Banda Aceh. The results of the study showed that based on partial significance tests, there was no significant effect of ability on employee performance, work motivation had an effect on employee performance, and job satisfaction had no effect on employee performance at PT. Telkom Akses Area Banda Aceh. Furthermore, collectively, Ability, Motivation, and Job Satisfaction had an effect on employee performance at PT. Telkom Akses Area Banda Aceh. This study contributes to the development of managerial policies and human resource management strategies, emphasizing the importance of enhancing employee motivation to support improved performance.